2017
DOI: 10.1093/biolre/iox076
|View full text |Cite
|
Sign up to set email alerts
|

The response of the innate immune and cardiovascular systems to LPS in pregnant and nonpregnant mice†

Abstract: Sepsis is the leading cause of direct maternal mortality, but there are no data directly comparing the response to sepsis in pregnant and nonpregnant (NP) individuals. This study uses a mouse model of sepsis to test the hypothesis that the cardiovascular response to sepsis is more marked during pregnancy. Female CD1 mice had radiotelemetry probes implanted and were time mated. NP and day 16 pregnant CD-1 mice received intraperitoneal lipopolysaccharide (LPS; 10 μg, serotype 0111: B4). In a separate study, tiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
4
13
2
Order By: Relevance
“…Moreover, noninflammatory effects of LPS‐induced systemic inflammation could be further explored. For instance, hemodynamic disturbances—as observed in several mice models upon LPS administration—might affect valve pathology . However, whether this leads to direct valve thickening remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, noninflammatory effects of LPS‐induced systemic inflammation could be further explored. For instance, hemodynamic disturbances—as observed in several mice models upon LPS administration—might affect valve pathology . However, whether this leads to direct valve thickening remains to be established.…”
Section: Discussionmentioning
confidence: 99%
“…This may relate to pregnancy-induced changes in the cardiovascular system or to an excessive response of the innate immune system to infection. Previously, we reported that the administration of the bacterial wall component, lipopolysaccharide (LPS), to pregnant mice resulted in marked hypotension, but had no effect in non-pregnant mice [3]. We extended these findings using caecal ligation and puncture (CLP), showing that pregnant mice had a more marked hypotensive response and a higher mortality [4].…”
Section: Introductionmentioning
confidence: 87%
“…However, since P4 alters both the maternal immune and cardiovascular systems, it is possible that it could change the maternal response to infection, potentially making women more susceptible to sepsis. In an earlier study, we reported that LPS administration induced a greater hypotensive response in pregnant compared to non-pregnant mice [3]. In this study, we have tested the hypothesis that P4 supplementation exacerbates this hypotensive response in pregnant mice and investigated potential causative mechanisms, studying aspects of the innate immune and the cardiac responses to LPS.…”
Section: Currently 17-ohpc Is Recommended By the American College Ofmentioning
confidence: 95%
“…The immune system of the mother during pregnancy is tightly regulated to prevent an unwanted immune response against the paternal antigens present in the developing conceptus (Racicot et al, 2014 ; Groen et al, 2015 ; Zöllner et al, 2017 ). As gestation progresses, there is suppression of the pro-inflammatory Th1 type of immunity and a shift toward a more anti-inflammatory, Th2 immune state in the mother (Saito et al, 2010 ), which supports fetal growth and maternal well-being (Mor and Cardenas, 2010 ).…”
Section: Adaptations In Maternal Physiology During Pregnancy and Lactmentioning
confidence: 99%